Multimedia classrooms of the secondary schools in Bangladesh: A situation analysis - Ropum, S. M. Kamruddin; Islam, Muhammad Monirul; Rabbi, Md. Fajlay (Journal of Research in Instructional, 2022)
As the multimedia classroom gained enormous importance from the government of Bangladesh to modernize the educational system, this study initiated the objective to investigate the state of those classrooms at secondary schools. The study used a mixed-method approach with qualitative and quantitative data to explore the execution and possible improvements for those multimedia classes. Five secondary schools were selected purposively from each of the two districts named Sylhet and Cumilla. From these ten schools, hundred students and hundred assistant teachers were selected randomly to conduct ten focus group discussions (FGD) with each of the two groups. Moreover, ten interviews were conducted with the head teachers. Besides those, classrooms were observed while the multimedia was in use, along with a case study in a school. Although head teachers and assistant teachers mentioned many classes using multimedia, the students' words and observed class information gave alternative facts. Almost similar types of outcomes were found regarding digital content development, monitoring, and mentoring activities. While teachers were optimistic about the quality of digital content and classroom teaching, researchers found those to be less standard. In terms of monitoring the multimedia classroom, the majority of head teachers were more concerned about the number of multimedia used in the classroom due to administrative obligations than the quality.